2022
DOI: 10.3389/fpls.2022.1005895
|View full text |Cite
|
Sign up to set email alerts
|

MtPT5 phosphate transporter is involved in leaf growth and phosphate accumulation of Medicago truncatula

Abstract: Phosphorus (P) is an indispensable mineral nutrient for plant growth and agricultural production. Plants acquire and redistribute inorganic phosphate (Pi) via Pi transporters (PHT1s/PTs). However, apart from MtPT4, functions of the M. truncatula (Medicago truncatula) PHT1s remain unclear. In this study, we evaluated the function of the PHT1 family transporter MtPT5 in M. truncatula. MtPT5 was closely related to AtPHT1; 1 in Arabidopsis (Arabidopsis thaliana) and GmPT7 in soybean (Glycine max). MtPT5 was highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…MtPT5 encodes a plasma membrane-localized Pi transporter (Liu et al, 2008). Ectopic expression of MtPT5 complements the Pi uptake capability in the Arabidopsis pht1;1pht1;4 double mutant, confirming its function in Pi uptake (Wang et al, 2022). In soybean, GmPT4 is a plasma membrane-localized Pi transporter; and overexpression of GmPT4 increases the growth and Pi uptake in soybean, improving PAE (Guo et al, 2022).…”
Section: Induction Of Phosphate Transporter Genesmentioning
confidence: 78%
See 1 more Smart Citation
“…MtPT5 encodes a plasma membrane-localized Pi transporter (Liu et al, 2008). Ectopic expression of MtPT5 complements the Pi uptake capability in the Arabidopsis pht1;1pht1;4 double mutant, confirming its function in Pi uptake (Wang et al, 2022). In soybean, GmPT4 is a plasma membrane-localized Pi transporter; and overexpression of GmPT4 increases the growth and Pi uptake in soybean, improving PAE (Guo et al, 2022).…”
Section: Induction Of Phosphate Transporter Genesmentioning
confidence: 78%
“…It has been demonstrated that the root-associated/secreted PAPs are either associated with root surfaces or secreted into the rhizosphere, scavenging Pi from external organic P and increasing Pi availability (Loṕez-Arredondo et al, 2014;Tian and Liao, 2015;Wang and Liu, 2018). The Pi-starvation-increased activity of root-associated/secreted acid phosphatase is observed in common bean, stylo and peanut (Arachis hypogaea) (Liang et al, 2010a;Wei et al, 2022;Liu et al, 2016Liu et al, , 2018.…”
Section: Root Exudatesmentioning
confidence: 99%
“…Excess Pi accumulates in the vacuole in tissues (Veneklaas et al, 2012) and in globular structures in roots (Ryan et al, 2019), which are the mechanisms of high P tolerance, and both these processes rely on P transporters to move P across membranes. As unigenes of phosphate transporters were upregulated in both Polygonum species by high‐P exposure (Supporting Information: Table ), Polygonum species might allocate high Pi into vacuoles by phosphate transporters to achieve tolerance to high P. Phosphate transporter MtPT5 plays a vital role in P accumulation, and overexpression of MtPT5 promotes leaf size of Medicago truncatula , accompanied with greater biomass and P accumulation (Wang et al, 2022b). Similarly, the high expression of phosphate transporters (Supporting Information: Table ) in leaves might contribute to leaf growth and account for the P hyperaccumulation and storage in Polygonum species.…”
Section: Discussionmentioning
confidence: 99%
“…Excess Pi accumulates in the vacuole in tissues (Veneklaas et al, 2012) and in globular structures in roots (Ryan et al, 2019), which are the mechanisms of high P tolerance, and both these processes rely on P transporters to move P across membranes. As unigenes of phosphate transporters were upregulated in both Polygonum species by high-P exposure (Supporting Information: Table S1 (Wang et al, 2022b). Similarly, the high expression of phosphate transporters (Supporting Information:…”
Section: F I G U R Ementioning
confidence: 96%
“…tereticornis under -P/-P conditions. On the contrary, the expression of PHT1.5 and PHT1.6 transporters were higher in the leaves of E. grandis plants under +P/+P conditions (Figures 5B, 5C), which may be related to P transport and remobilization (Wang et al 2022). In Medicago truncatula the PHT1 transporter MtPT5 was proved to play an important role in leaf growth and Pi accumulation (Wang et al 2022).…”
Section: Genes Related To Transport and Uptake P (Pht1 And Pho1)mentioning
confidence: 94%